Stanowisko głównych polskich ugrupowań socjalistycznych w Łodzi w latach 1905–1907 wobec kwestii autonomii Królestwa Polskiego - Markiewicz, Grzegorz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The events which took place in 1905–1907 in the Kingdom of Poland were to inspire insurgent activities in order to regain independence or bound to institutional and social change. Łódź was area about particularly an intense strike movement. The number of political parties have conducted propaganda activity. Rivalry between PPS and SDKPiL played the special roll. For the entire period revolutionary only SDKPiL talked consistently himself too autonomy of the Kingdom of Poland towards Russia. Aspiring to the socioeconomic revolution, she rejected the idea of the independence of Poland for ideological reasons. PPS consistently was in favour of an idea of the independence of Poland and wanted to convert the revolutionary move into the armed insurrection. However this current didn’t play a major role on Łódź. Local PPS it the one as a result of the progressing schism this party wasn’t able to decide or in the Kingdom to grant revolutionary or insurrectionary character a grassroots movement.